Aplikasi Tahu dan Daun Kelor (Moringa oleifera) Pada Nugget - Timur Ina; Utari Krisnandani; I Gusti Ayu Ekawati (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2016)
The aim of this research was to know the influenceof tofu and moringa leaf comparison to the characteristic of nugget and to know the best comparison of nugget. The experimental design used in this research was randomized block design (RBD), by treatment comparison of tofu and moringa leaf , that is 97% tofu : 3% moringa leaf, 94% tofu :6% moringa leaf, 91% tofu : 9% moringa leaf, 88% tofu : 12% moringa leaf, 85% tofu : 15% moringa leaf, 82% tofu : 18% moringa leaf. All of those treatments were repeated for 3 times to obtain 18 research units. Data were analyzed using analysis of variance and if influence occurred among the treatments, the data will be processed using Duncan’s test. Results of this research had shown that the comparison ratio of tofu and moringa leaf gave influence to the water content, protein content, vitamin C content, antioxidant capacity, ash content, color, and taste. The best treatment was the nugget using 82% tahu and 18% moringa leaf, with 22,53% water content, 2,34% ash content, 10,13% protein content, 18,10% vitamin C content, 73,53 mg/L GAEAC antioxidant capacity, color, texture, aroma , taste , and overall acceptance with the like criteria.